Improving reporting of exercise capacity across age ranges using novel workload reference equations - Santana, Everton Jose; Christle, Jeffrey W.; Cauwenberghs, Nicholas; Peterman, James E.; Busque, Vincent; Gomes Botelho Quintas, Bruna; Bagherzadeh, Shadi P.; Moneghetti, Kegan; Kuznetsova, Tatiana; Wheeler, Matthew; Ashley, Euan; Harber, Matthew P.; et al. (The American journal of cardiology, 2024)
Exercise capacity (EC) is an important predictor of survival in the general population and in subjects with cardiopulmonary disease. Despite its relevance, considering the percent-predicted workload (%pWL) given by current equations may overestimate EC in older adults. Therefore, to improve the reporting of EC in clinical practice, our main objective was to develop workload reference equations (pWL) that better reflect the relation between workload and age. Using the Fitness Registry and the Importance of Exercise National Database (FRIEND), we analyzed a reference group of 6,966 apparently healthy participants and 1,060 participants with heart failure who underwent graded treadmill cardiopulmonary exercise testing. For the first group, the mean age was 44 years (18 to 79); 56.5% of participants were males and 15.4% had obesity. Peak oxygen consumption was 11.6 ± 3.0 METs in males and 8.5 ± 2.4 METs in females. After partition analysis, we first developed sex-specific pWL equations to allow comparisons to a healthy weight reference. For males, pWL (METs) = 14.1−0.9×10−3×age2 and 11.5−0.87×10−3×age2 for females. We used those equations as denominators of %pWL, and based on their distribution, we determined thresholds for EC classification, with average EC defined by the range corresponding to 85% to 115%pWL. Compared with %pWL using current equations, the new equations yielded better-calibrated %pWL across different age ranges. We also derived body mass index-adjusted pWL equations that better assessed EC in subjects with heart failure. In conclusion, the novel pWL equations have the potential to impact the report of EC in practice.
Online verfügbar: 30. Januar 2024, Artikelversion: 6. Februar 2024
Gesehen am 23.08.2024